VALUE THEORY AND THE BEST INTERESTS STANDARD1 - Degrazia, David (Bioethics, 1995)
The idea of a patient's best interests raises issues in prudential value theory–the study of what makes up an individual's ultimate (nonmoral) good or well-being. While this connection may strike a philosopher as obvious, the literature on the best interests standard reveals almost no engagement of recent work in value theory. There seems to be a growing sentiment among bioethicists that their work is independent of philosophical theorizing. Is this sentiment wrong in the present case? Does value theory make a significant difference in interpreting best interests? In pursuing this question, I begin with a quick sketch of broad kinds of value theories, identifying representatives that are plausible enough to count as contenders. I then explore what each account suggests in (1) neonatal treatment decisions, and (2) decisions for patients in persistent vegetative states. I conclude that while these accounts converge somewhat in their interpretations of best interests, they also have importantly different implications.